Beethoven. Rede, gehalten an der Beethovenfeier des Lesezirkels Hottingen in Zürich am 10. Dezember 1920 - Hofmannsthal, Hugo von 1874-1929; Schuh, Willi (Wien Leipzig Zürich Reichner, 1938)
Throughout his writing career, Hofmannsthal constantly refers to Beethoven, whose work always seemed to him highly vivid and modern at a time when, in his opinion, a great unifying European figure is sorely lacking. In the speeches he dedicates to him in 1920 for his 150th birthday, he particularly examines the situation of Beethoven in Vienna. The eulogy of the composer, in the disturbed context of the first decades of the 20th century, thus responds to several issues: Hofmannsthal consecrates Beethoven as a poet; in accordance with the titanic imagery developed throughout the 19th century and with a literary, political, mythological or biblical imagination, he makes of him one of the greatest myths of Europe and one of the major guiding figures of his Europeanist commitment.
Afterword by editor W. Schuh, german Musicologist, NZZ editor, Schoeck pionier & Strauss biographer
Throughout his career as a critic and lecturer, Hofmannsthal constantly referred to Beethoven as one of the great tutelary figures of nineteenth-century European artistic life. In 1920, on the occasion of the composer's one hundred and fiftieth birthday celebrations, he dedicated two texts to him: the so-called ‘Zurich speech’ (Zürcher Rede auf Beethoven), delivered on 10 December of the same year at a ceremony organised by the Hottingen reading circle, greeted by an audience of 2,400 people5 and published on 19 December in the Neue Zürcher Zeitung, and a shorter and substantially different version of this speech (Rede auf Beethoven), published on 12 December in the Neue Freie Presse. In these texts, in which Hofmannsthal did not fail to underline the perhaps paradoxical dimension of choosing an Austrian poet to pay tribute to a German composer6 , it is Beethoven's situation in Vienna that is questioned.As he wrote to Ernst Benedikt on 11 March 1927, Hofmannsthal confessed that he had only accepted the invitation to give this speech out of patriotism, despite his initial reluctance due to his lack of musical skills7 : ‘The German position in the world at the time was so pitiful, and the German attitude so undignified, that I found it necessary to seize every opportunity to express a dignified and serious sense of self. ’
https://journals.openedition.org/austriaca/5084
Keywords: Beethoven, Ludwig van -- 1770-1827; 20th Century (1901-2000); Composer; Legacy; Eulogy